Nurses' perception about skin injuries in a pediatric hospital in the northeastern countryside (Research, Society and Development, 2022)
This study aimed to identify nurses' perception of skin lesions developed in a pediatric hospital in Salvador Bahia. Method: This is a qualitative research, and, in the data collection, we used the interview with a previously prepared script and the discourse analysis to systematize the material obtained. Results: the data show that nurses have mastery of techniques for injury prevention and highlight the importance of continuing education in health care. Conclusion: The peculiarities of the professionals interviewed make it possible to identify individuals who graduated for more than 2 years, 90% female and 70% aged between 31 and 40 years. Through the speeches, the importance of EFA in such injuries was observed, with the main objective of nutrition and hydration of the wound, corroborating the findings in the literature. support in decision making. It was noticed the need for continuing education mainly due to the constant changes in health, an effective skin commission to support and guide these lesions and it was observed through the speeches that the absence of materials can harm the continuity of treatment.